(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Parkinson's Disease (PD) is the second most common neurodegenerative disorder. Its risk increases with advancing age. Prevalence of Parkinson’s disease in Pakistan has been estimated to be 0.4 million by Pakistan Parkinson Disease Society.[1] The exact etiology has not been fully elucidated but there is evidence of involvement of non-dopaminergic pathways (such as cholinergic and serotonergic). Non-motor symptoms (NMS) often precede motor symptoms by up to several decades, most commonly olfactory dysfunction (hyposmia), Rapid Eye Movement (REM) sleep behavior disorder (RBD), constipation, depression, and pain.[2] The NMS of parkinsonism can occur both during early and late stage and are due to non-dopaminergic cell dysfunction such as serotonin.[3]